2016
DOI: 10.18805/lr.v0iof.10282
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of Aphis craccivora (Koch) and its natural enemies on bean crop in relation to weather parameters in Vadodara, Gujarat, India

Abstract: The studies on the population dynamics of Aphis craccivora (Koch) were conducted during 2008-2011. This pest is a serious pest in the agricultural fields of Vadodara, India. The results showed that the aphid population was higher in the month of September to January on bean crop. The maximum population of Aphis craccivora (Koch) was seen in the month of January to March. The correlation of the aphid population was done with abiotic and biotic factors. The aphid population was showing positive correlation with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 9 publications
4
7
0
Order By: Relevance
“…Similarly, Bajia and Singh (2014) found that the coccinellid population was greatly influenced by different weather parameters and reported that the maximum and minimum temperature showed a positive correlation with the coccinellids population, whereas relative humidity had a negative correlation. The present findings are in partial accordance with the findings of Kataria and Kumar (2016) who reported that the ant population on cowpea showed a negative correlation with maximum and minimum temperature.…”
Section: Over Yearssupporting
confidence: 93%
See 1 more Smart Citation
“…Similarly, Bajia and Singh (2014) found that the coccinellid population was greatly influenced by different weather parameters and reported that the maximum and minimum temperature showed a positive correlation with the coccinellids population, whereas relative humidity had a negative correlation. The present findings are in partial accordance with the findings of Kataria and Kumar (2016) who reported that the ant population on cowpea showed a negative correlation with maximum and minimum temperature.…”
Section: Over Yearssupporting
confidence: 93%
“…The pest population was very low at the time of crop harvesting during 8 th SMW and these were 9.38 and 4.26 per 30 cm apical shoot per plant in variety KPMR 935 and IFPD 122, respectively. The results are in partial agreement with Kataria and Kumar (2016), who found that maximum infestation of A. craccivora occurred in February to March on cowpea in Gujarat. The results are also more or less in agreement with Srikanth and Lakkundi (2014), who stated that the population of A. craccivora on cowpea increased rapidly with crop growth and their peak coincided with peak pod formation which may be due to higher availability of quality proteins in the plant and is very essential for aphid multiplication.…”
Section: Seasonal Incidence Of Pulse Aphid and Its Natural Enemies Onsupporting
confidence: 91%
“…The value of coefficient of determination R 2 revealed that the seasonal incidence of bean aphid was influenced by weather parameters to the extent of 86.70 per cent (Table 3). This result is in close conformity with the findings of Kataria and Kumar (2016) who studied the seasonal incidence of A. craccivora on bean crop. They reported that the maximum population of pest was seen in the month of January to March.…”
Section: Impact Of Weather On Aphid Populationsupporting
confidence: 92%
“…Regarding aphid abundance dynamics, relative humidity had higher explicative power than other climatic indicators (precipitations, temperature) [ 31 , 32 ]. Natural enemy abundance was more predictive of aphid abundance dynamics than aphid density [ 33 ], but less important than crop type [ 34 ] or climatic indicators [ 31 ].…”
Section: Resultsmentioning
confidence: 99%